INCREASING RECOMBINANT PENICILLIN G ACYLASE PRODUCTION: GENETIC, PROTEIN ENGINEERING, AND PRODUCTIVITY IMPROVEMENT - Dini Achnafani; Gabriela Christy Sabbathini; Sri Rezeki Wulandari; Maria Ulfah; Nurul Apsari Aji; Niknik Nurhayati; Haniyya Haniyya; Is Helianti (Balai Bioteknologi, Badan Pengkajian dan Penerapan Teknologi (BPPT), 2022)
ABSTRACT B-lactam derived antibiotics are the most used globally for treatment against different infections caused by pathogenic bacteria and comprises 65% of the world antibiotics. Recently, penicillin G acylase (PGA) is used as biocatalyst for those B-lactam antibiotics production by which 6-aminopenicillanic acid (6-APA) or 7-aminodeacetoxycephalosporanic acid (7-ADCA) as the building blocks is produced. Commercialized PGA from native microbial resources are still limited to E. coli. Therefore, genetic engineering approach such as cloning and expression in other microbial hosts were assessed to enhance bacterial strains that produce PGA. However, such improvement could increase immature precursors accumulation and lowering the enzyme yield, activity, or stability. This review focus on the review of PGA recombinant produced by several microbial host, their expression levels, and improvement achieved by some modification such as replacement of signal peptide and promoter continued to protein engineering to utilize the enzymes in synthetizing amoxicillin rather than to hydrolyses Penicillin G. ABSTRAK Antibiotik turunan B-laktam adalah kelompok antibiotik yang paling banyak digunakan dalam pengobatan infeksi bakteri patogenik dan mencakup 65% dari penggunaan antibiotik di seluruh dunia. Enzim Penisilin G Asilase (PGA) digunakan sebagai biokatalis dalam produksi senyawa bahan baku antibiotik B-laktam berupa asam-6-aminopenisilinat (6-APA) dan asam-7-aminodeasetoksisefalosporanat (7-ADCA). Enzim PGA komersial masih sangat terbatas dan lebih banyak bersumber dari E. coli. Peningkatan produksi PGA dapat dilakukan melaui rekayasa genetika seperti kloning dan ekspresi PGA dengan menggunakan mikroorganisme lain. Namun demikian, rekayasa tersebut dapat menyebabkan akumulasi prekursor dalam sel yang mengakibatkan rendahnya perolehan enzim yang didapat, maupun rendahnya aktivitas dan stabilitas enzim. Tinjauan ini berfokus pada potensi peningkatan produksi PGA rekombinan dari berbagai sel mikroorganisme yang dapat dicapai melalui modifikasi sekuens sinyal peptida dan promoter hingga rekayasa protein dengan tujuan mendapatkan enzim PGA untuk sintesis antibiotik amoksisilin daripada hidrolisis PGA.